Pogranicze i prowincja kontra prowincjonalizm. Lekcja Krzysztofa Czyżewskiego - Korwin-Piotrowska, Dorota (Tematy i Konteksty, 2019)
The paper concerns a book by Krzysztof Czyżewski entitled A Small Center of the World and the issues presented in it, namely those of borderland and province, of the merging of various cultures, nationalities, traditions, and religious beliefs within one space. Czyżewski is the initiator, founder, and for almost three decades an employee of the Borderland Foundation and Center in Sejny, as well as of the nearby International Center for Dialogue in Krasnogruda (both localities are situated close to the Polish-Lithuanian border). As a “practitioner of ideas”, as he tends to call himself, Czyżewski casts a new light on the issue of province by pointing out that thanks to caring for one’s own roots and for the local, it may become possible to prevent the provincialism of thinking, and that the possibilities of overcoming inter-human division accumulate in the „small centers of the world”. The paper does not only discuss the issues which are focused on in the book in question, but also refers to other works dedicated to borderlands and to the current cultural situation in Poland.